Reforming the North: the kingdoms and churches of Scandinavia, 1520-1545 - Larson, James (Cambridge University Press, 2010)
The turbulence of the Protestant Reformation marks a turning point in European history, but the Scandinavian contribution to this revolution is not well known outside the Northern world. Reforming the North focuses on twenty-five years (1520–45 AD) of this history, during which Scandinavians terminated the medieval Union of Kalmar, toppled the Catholic Church, ended the commercial dominance of the German Hanse, and laid the foundations for centralized states on the ruins of old institutions and organizations. This book traces the chaotic and often violent transfer of resources and authority from the decentralized structures of medieval societies to the early modern states and their territorial churches. Religious reform is regarded as an essential element in the process - in the context of social unrest, political conflict, and long-term changes in finance, trade, and warfare. Reforming the North offers a broad perspective on this turbulent period and on the implications of the Protestant Reformation for Northern history.